2018
DOI: 10.3390/coatings8080284
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-Modified SnO2/Metglas Electrodes for the Simultaneous Electrochemical and Magnetoelastic Sensing of H2O2

Abstract: In this work, we present a simple and efficient method for the preparation of hemin-modified SnO2 films on Metglas ribbon substrates for the development of a sensitive magneto-electrochemical sensor for the determination of H2O2. The SnO2 films were prepared at low temperatures, using a simple hydrothermal method, compatible with the Metglas surface. The SnO2 film layer was fully characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), photoluminescence (PL) and Fourier Transform-Infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Other TCO-based electrochemical sensors with hemin involved its immobilization on SiO 2 -modified iron oxide particles [ 153 ] or mesoporous SnO 2 on ITO grafted on a polyethylene terephthalate support, creating a flexible sensor for hydrogen peroxide [ 154 ]. The latter approach was further modified by the same group around Topoglidis using Metglas ribbons as support, thus enabling electrochemical as well as magnetoelastic sensing of hydrogen peroxide [ 155 ]. Unfortunately, the peroxide determination had to be performed at negative potentials in these systems, although some previous studies on gold and carbon have demonstrated that the direct electrocatalytic reduction of hydrogen peroxide by immobilized hemin can proceed at high potentials similar to heme peroxidases [ 44 , 148 , 156 ].…”
Section: Peroxidase Reactions On Semiconductors For Electrochemicamentioning
confidence: 99%
“…Other TCO-based electrochemical sensors with hemin involved its immobilization on SiO 2 -modified iron oxide particles [ 153 ] or mesoporous SnO 2 on ITO grafted on a polyethylene terephthalate support, creating a flexible sensor for hydrogen peroxide [ 154 ]. The latter approach was further modified by the same group around Topoglidis using Metglas ribbons as support, thus enabling electrochemical as well as magnetoelastic sensing of hydrogen peroxide [ 155 ]. Unfortunately, the peroxide determination had to be performed at negative potentials in these systems, although some previous studies on gold and carbon have demonstrated that the direct electrocatalytic reduction of hydrogen peroxide by immobilized hemin can proceed at high potentials similar to heme peroxidases [ 44 , 148 , 156 ].…”
Section: Peroxidase Reactions On Semiconductors For Electrochemicamentioning
confidence: 99%
“…This Special Issue, entitled "Mesoporous Metal Oxide Films" contains a collection of ten research articles covering fundamental studies and applications of different metal oxide films. Going into detail, Samourganidis et al [8] investigated the use of a Metglas ribbon substrate modified with a hemin SnO 2 coating for the development of a sensitive magneto-electrochemical sensor for the determination of H 2 O 2 . The mesoporous SnO 2 films were prepared at low temperatures, using a simple hydrothermal method that is compatible with the Metglas surface.…”
Section: This Special Issuementioning
confidence: 99%
“…It is an iron-nickel alloy with high corrosion resistance that is typically formed into thin foils or ribbons. It is extremely flexible and strong due to its geometry and elasticity, and it has many applications in sensing research [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%